Case Report: Intraoperative Open-Heart Coronary Angiography in Acute Type A Aortic Dissection - Yang, Jue; Li, Xin; Chen, Zerui; Sun, Tucheng; Fan, Ruixin; Yu, Changjiang (Frontiers in Cardiovascular Medicine, 2021)
For patients with acute type A aortic dissection, strongly suspected of having concomitant severe coronary artery disease (CAD), preoperative or intraoperative coronary angiography has been recommended. However, conventional selective coronary angiography in this setting may extend the dissection or aortic rupture. We present the use of intraoperative open-heart coronary angiography in a patient with acute type A aortic dissection. A 50-year-old man presented with chest pain and dyspnea and was admitted to our department with acute type A aortic dissection. The patient underwent coronary artery stent implantation in the left anterior descending coronary artery (LAD) 3 years previously due to an acute myocardial infarction. This time we failed to evaluate the patency of the LAD using multidetector computed tomography. An aortic rupture occurred due to conventional coronary angiography, and open-heart coronary angiography was performed. The examination revealed no significant stenosis. A Bentall procedure and total aortic arch replacement were performed, with an intraoperative stent inserted into the descending aorta, and the patient had an uneventful postoperative course. From this case, we learn that intraoperative open-heart coronary angiography is safe and effective in patients with acute type A aortic dissection.